A case of infectious mononucleosis complicated with spontaneous atraumatic splenic rapture caused by Epstein–Barr virus infection. Issue 12 (5th September 2022) - Lu, Qiliang; Fu, Wen; Ouyang, Guangxiong; Xu, Qiuran; Huang, Dongsheng
Abstract: Splenic rupture is the most serious complication of infectious mononucleosis (IM) caused by Epstein–Barr virus (EBV) infection, with a mortality rate of over 1 in 10. We reported a case of spontaneous atraumatic splenic rupture secondary to IM in a young man. The patient presented with abdominal pain caused by splenic rupture as the initial symptom. The diagnosis and treatment process went through a series of twists and turns, including the emergency department, general surgery department, and infection department. This case suggests that clinicians should consider the possibility of EBV infection in young patients with spleen rupture without obvious cause to avoid misdiagnosis and missed diagnosis.